THE MODERNIZATION OF TEACHING IN UNDERGRADUATE TEACHER TRAINING FOR PRIMARY SCHOOL - RASKOVA, Miluse (Trends in education, 2010)
The contribution informs about activities, which already support improving of teachers extasciiacute academic preparation at Pedagogical faculty of Palacky University in Olomouc. Further it attention to new study material production of multimedia character, which like other modern schooling resource contribute markedly to deepen and improving of future teachers extasciiacute professional preparation in the kindergarten and in the primary school in environmental education domain.
Keywords: a new didactics extasciiacute instrument; complex teaching methods; the project teaching.